Implementation of Occupational Safety Standards by Public Area Attendants at Department Style Hotels in Bali - Putu Bella Anggreni; Ni Ketut Iswarini; Pitanatri, Made Uttari (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the implementation of occupational safety standards by public area attendants, Department Style Hotel X. Data collection techniques include observation, interviews, and documentation studies. Data analysis was carried out using descriptive comparative qualitative methods between high-risk occupational safety standards (High Risk Task) and their implementation by public area attendants, Department Style. The results of the study showed that full compliance (100%) in maintaining cleanliness and dryness of the floor, installing